Acesso a ações e serviços de saúde da atenção primária durante a pandemia de Covid-19: a experiência de um município do interior da Bahia - Almeida, Silvani Silva de (2023)
The universalization of access to health in Brazil brought with it the need to reorganize and expand health services. In this context, PHC has become a government priority in the reorientation of health policies at the local level, with the aim of strengthening the “gateway” of the SUS. Thus, this study aimed to analyze access to PHC health actions and services during the Covid-19 pandemic (2020-2022), in a municipality in the interior of Bahia. The research was carried out in the municipality of Retirolândia - Bahia - Brazil, which is part of the Sisal identity territory, being part of the Serrinha micro-region. This is a qualitative, exploratory study that used a semi-structured interview as a data collection instrument. The data analysis method was thematic content analysis. The participants were managers and health workers linked to the Municipal Health Department, in a total of four participants. The results show that the access flow of users to PHC before the pandemic was predominantly spontaneous and, during the pandemic, almost exclusively by appointment, this was carried out with the support of the CHA. The actions and health services that had their offer restricted by the covid-19 pandemic were: assistance to users with hypertension and diabetes and prenatal consultations. In this sense, some strategies were used to maintain and/or expand users' access to actions and health services offered by the PHC, among them the resizing of service hours, use of telehealth, social networks, and the CHA's ability to articulate with the community, the latter a lightweight technology that is extremely efficient in communicating with users. Such findings can contribute to a reflection on the PHC organization process and its fundamental role as a reorganizer of the health care network. This study has some limitations, such as the small number of respondents and the overlapping roles of some participants, both managers and network workers.